JAVA COASTAL COMMUNITY EMPOWERMENT MODEL - Abdul Aziz; Akhmad Shodikin; Mohammad Rana (IAIN Syekh Nurjati Cirebon, 2019)
Abstract: Speaking of the northern coastal communities of Java (Pantura), the first thing that comes to mind is the fishing community. The fishing community has always been an interesting object to learn. This is because the condition of the fishing area is different from the natural resources (SDA) of the sea owned by the northern coast of Java. The fishing area is always synonymous with poverty and backwardness in the midst of abundant marine wealth. However, this hypothesis is not entirely true, because not all northern coastal areas of Java are in that condition. This is of course because each region has different policies and concerns from the government of the shelter, but the most important factor is the willingness and determination of the local people in the northern coast to empower themselves.Keywords: Empowerment, Communities, Coastal, Java